PENGARUH SUKU BUNGA KREDIT DAN PRODUK DOMESTIK BRUTO TERHADAP PENYALURAN KREDIT PERBANKAN BANK UMUM PEMERINTAH DI INDONESIA - Susi Ramelda; Tri Sukirno Putro; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how much influence lending rates, and gross domestic product of the banking credit to the general government bank in Indonesia in 2002-2011. This study uses a quantitative method, and analyzed using multiple linear regression analysis using a computer application SPSS 20 for windows. In this study, the independent variables namely Lending Rates (X1), Gross Domestic Product (X2), while the dependent variable is Lending Banking (Y). Variable interest rates on working capital loans (X1) has a negative regression coefficient of -0.004 to total working capital loans. Variable interest rates on investment loans (X1) has a positive regression coefficient of -0.001 to total loan investments. Variable interest rates on consumer credit (X1) has a negative regression coefficient of -0.064 to total consumer loans. Variable gross domestic product (X2) has a positive regression coefficient for 7,615E-007 on the growth of working capital loans. Variable gross domestic product (X2) has a positive regression coefficient for 5,094E-007 on the growth of investment credit. Variable gross domestic product (X2) has a positive regression coefficient for 6,499E-007 on the growth of consumer credit. It can be concluded that the GDP is positive and significant effect on lending. Simultaneously, the variable lending rates and gross domestic product have a significant effect on bank lending of commercial banks in the Indonesian government.Keywords : Lending, Interest Rates, and GDP